Implementation of Using Used Materials and Natural Materials as Learning Media in Improving Cognitive Development - Khairuni Siregar; Hafsah Hafsah; Farida Jaya (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This article aims to describe the implementation of the use of used materials and natural materials as learning media in improving cognitive development at RA(kindergarten) Munawwarah Medan. The focus of the study described in this article includes the ability of teachers to design teaching materials sourced from natural and used materials, the learning process, and improving the cognitive competence of students. This study uses a qualitative approach with a descriptive method. The process of collecting data was carried out qualitatively by means of observation, interviews, and document studies. Then, the data were analyzed through data reduction techniques, data presentation, and drawing conclusions. The results of this article found that (1) the teacher's ability is fairly good in designing teaching materials sourced from natural and used materials, this is evidenced by the readiness of teacher learning plans; (2) the implementation of learning takes place effectively, marked by the suitability of the plans that have been made previously with the learning implementation process, as well as the process of learning activities using natural materials and used materials, starting from initial activities, core activities to closing activities; and (3) the cognitive competence of students at RA Munawwarah Medan is increasing well, marked by the child's ability to mention numbers, know the concept of numbers, be able to sort objects from smallest to largest, group objects according to type and color, and mention the function of an object.